Voltage-gated potassium channels (Kv) in GtoPdb v.2021.3. (2021) - Attali, Bernard; Chandy, K. George; Giese, M. Hunter; Grissmer, Stephan; Gutman, George A.; Jan, Lily Y.; Lazdunski, Michel; Mckinnon, David; Nerbonne, Jeanne; Pardo, Luis A.; Robertson, Gail A.; Rudy, Bernardo; et al.
No abstract available